The Evolution of Orthodontics: Advancements, Innovations, and Transformative Technologies (Academia Journal of Medicine, 2022)
This paper explores the remarkable advancements  that have reshaped the field of orthodontics, ushering  in an era of precision, efficiency, and patient-centered  care. From digital technology and invisible  orthodontic solutions to 3D printing and AI-driven  treatment planning, the evolution of orthodontics has  redefined treatment strategies and enhanced clinical  outcomes. This comprehensive review highlights the  transformative technologies that have revolutionized  orthodontic practice, ultimately improving patient  experiences and treatment effectiveness.
Keywords: Orthodontics; Orthodontic treatment; Recent innovations